2023
DOI: 10.1038/s41598-023-48864-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of the mulligan maneuver for cervicogenic headache: a randomized controlled trial

Xin Jin,
Hong-Gen Du,
Ning Kong
et al.

Abstract: Cervicogenic headache is an often observed secondary headache in clinical settings, with patients who endure prolonged and persistent pain being particularly susceptible to mood changes. Currently, the Mulligan is one of the effective methods for CEH. However, there is a lack of evaluation about the strength and frequency of headaches, as well as the assessment of pain-induced emotions, in individuals with CEH using this particular procedure. Herein, we aimed to evaluate the effectiveness of the Mulligan maneu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Activation of sgACG in chronic cluster headache patients using transcranial direct current stimulation improved their clinical symptoms ( 16 ). The Mulligan manoeuvre can improve pain levels by modulating the function of the frontal lobe and middle temporal gyrus related brain regions in patients with cervicogenic headache, and has a moderating effect on pain-related negative emotions ( 17 ). Meta-analysis showed that pain-related anxiety is characterised by neural activation in the inferior frontal gyrus, medial superior frontal gyrus, postcentral gyrus, MTG, parieto-occipital sulcus and striatum ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of sgACG in chronic cluster headache patients using transcranial direct current stimulation improved their clinical symptoms ( 16 ). The Mulligan manoeuvre can improve pain levels by modulating the function of the frontal lobe and middle temporal gyrus related brain regions in patients with cervicogenic headache, and has a moderating effect on pain-related negative emotions ( 17 ). Meta-analysis showed that pain-related anxiety is characterised by neural activation in the inferior frontal gyrus, medial superior frontal gyrus, postcentral gyrus, MTG, parieto-occipital sulcus and striatum ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“… Postoperative wound complications and acute pressure ulcers were recorded. The Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale (HAMD) and visual analogue scale (VAS) scores 18 : The HAMA scale consists of 14 items. Each item is scored on a 5‐point scale from 0 to 4, with higher scores indicating greater anxiety.…”
Section: Methodsmentioning
confidence: 99%